Experience of Female Urogenital Fistula – a Shift of Dominance From Obstetric Variety to Iatrogenic One (Bangladesh Journal of Urology, 2020)
Aim: This retrospective study was carried out in Jessore Medical College Hospital and Jhenidah District Hospital on different types of female urogenital fistulae to evaluate its aetiological aspect in the present health care scenario of the country.Materials and Methods: Female patients presenting with features of urogenital fistula were evaluated properly and operated through intra-abdominal and vaginal route depending upon the merit of the fistula. Aetiological pattern of the cases was evaluated along with surgical outcome and post-operative complications.Result: Ofthe 28 female urogenital fistulas, 27 (96.43%) were VVF and 1(3.57%) was UVF. Out of 28 cases, 71.42 %( 20patients) were post-hysterectomy complication, 21.42 %( 6 patients) cases resulted from birth trauma and 7.14 %(n=2) cases were post caesarean complication. Trans-abdominal route was used for operation in 22 (78.56%) cases while 6 (21.42%) cases were operated through trans-vaginal route. In this series of 28 cases, 89.29 %( 25 cases) patients were fully cured and10.71 %( 3cases) patients experienced recurrence.Conclusion: The aetiological pattern of the female urogenital fistula in our country has changed substantially from the dominance of birth trauma to post hysterectomy indicating a remarkable improvement in maternal care system along with development of other socioeconomic parameters.Bangladesh Journal of Urology, Vol. 21, No. 2, July 2018 p.71-75